Pemanfaatan Informasi Geospasial Dasar (IGD) untuk Analisis Penyimpangan Arah Kiblat Bangunan Masjid secara Masal - Yoga Kencana Nugraha; Aisah Hajar (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
Basic geospatial information that has been widely disseminated to the general public needs to be utilized optimally for various purposes related to spatial analysis. The city of Bandung is one of the cities with the largest muslim population and the largest mosque building in Indonesia. This study aims to analyze the mass deviation of the direction of mosque buildings, especially those that have been established in Cibeunying Kidul District, Bandung City. The method used is geovisual analysis by comparing the direction of the mosque's qibla which is calculated using the vincenty method to the direction of the mosque building obtained from the 1:1.000 scale RBI map, orthophoto and Mosque Information System (SIMAS). The calculation results show that only the Al Balad Mosque building leads to the city of Mecca. The average magnitude of the deviation from the qibla direction of the mosque building to the Kaaba is 150 1' 0,365